Towards Enhancing Effective Instructional Supervision in Technical Colleges in Ogun State, Nigeria - Oke, Jonathan O.; Olakotan, Olusegun O. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
Instructional supervision in schools in general and technical colleges in particular is a precursor to goal attainment. This study focused on enhancing effective instructional supervision in Ogun State technical colleges. Being a descriptive research of the survey type, the study raised two research questions focusing on activities for enhancing effective instructional supervision in technical colleges and mechanisms for enhancing effective instructional supervision in technical colleges. Also, two null hypotheses tested at 0.05 significant level were formulated. The instrument developed and used for the study was the Effective Instructional Supervision Questionnaire (EISQ). The EISQ contained 22 items which was validated by three experts, and tested to obtain 0.92 reliability coefficient using Cronbach Alpha method. The EISQ was used for collecting data from 21 respondents made of technical college administrators in Ogun State. The data collected were descriptively analyzed using mean for the raised research questions and inferential statistics of t-test for the formulated hypotheses. The study recognized the potency of instructional supervision and the need for embracing it in Ogun State technical colleges. The study recommended that technical college administrators should ensure effective instructional supervision in Ogun State technical colleges for overt instructional improvement and as well adopt global best practices to ensure that teachers are motivationally carried along in instructional supervision activities.